The friendship paradox in species-rich ecological networks: Implications for conservation and monitoring. (May 2017) - Pires, Mathias M.; Marquitti, Flavia M.D.; Guimarães, Paulo R.
Abstract: A great challenge in ecology and conservation biology is to deal with the inherent complexity of ecological systems. Because species are embedded in species-rich systems characterized by multiple interactions, it is often hard to identify which species are really important for ecological processes such as pollination. Here we show that species-rich networks describing plant-pollinator interactions share a property with networks depicting social relationships, the friendship paradox, which allows identifying highly-connected species without detailed information on the whole network of interactions. Numerical simulations support that the identified species are those more likely to affect community structure and ecological dynamics. A sampling protocol taking into account the friendship paradox property could be adapted to field studies, helping in the search for conservation surrogates or to monitor changes in the communities, such as functional extinction or the increase in ecological importance of invasive species. We hypothesize that the friendship paradox is likely to arise in networks describing other types of ecological interactions. Besides being useful for conservation and ecosystem management, the friendship paradox may have relevant implications in other areas of biology as well. Highlights: Communities form complex networks with multiple connections between species. Identifying which species are central in ecological networks is difficult. The friendship paradox is a property present in social and ecological networks. It allows identifying ecologically important species with limited information. The friendship paradox may help defining surrogate species and system monitoring.